A Comparison of Kinesiology and Athletic Taping on Ankle Range of Motion. Issue 3 (14th September 2018) - Folmar, Eric; Thomas, Adam
Category: Other Introduction/Purpose: A high prevalence of ankle sprains exists in athletic and non-athletic populations. White athletic tape (WAT), commonly used for prevention and treatment, provides ankle stability while limiting mobility. Athletic taping has demonstrated the ability to limit ROM in all directions, particularly ankle inversion, as inversion injuries represent a vast majority of ankle sprains. Use of kinesiology taping (KT) for the purpose of limiting mobility in the ankle has not been examined. While limiting inversion range of motion may be beneficial in prophylactic management of ankle injuries, limiting ROM in other directions may impact kinematics of other joints in the kinetic chain. To determine the effectiveness of an innovative KT technique for limiting ankle inversion ROM while allowing movement in the other movements of the ankle. Methods: Fifty-three healthy 18-25 year old college students were recruited for this study. Subjects received each of the taping conditions (traditional basket weave WAT, a novel KT method, and no tape) in a randomized order. Manual goniometer measurements were taken in non-weight bearing in the inversion, eversion, dorsiflexion and plantarflexion directions. A handheld inclinometer was used to measure weight bearing ankle dorsiflexion. Measures for each were compared across each taping condition. A repeated measures ANOVA was performed. Results: Significant decreases in ankle ROM (p <.01) were observed in all measures between WAT and no tape. KT demonstrated significant decreases in all ROM compared to no tape (p <.01), except for a minimal decrease in weight bearing ankle dorsiflexion (p>.05). WAT demonstrated significantly greater ROM restriction in all directions than did KT (p<.01), including weight-bearing ankle DF. Conclusion: These results suggest that KT allows for more ankle ROM than traditional WAT in non-weight bearing and weight bearing measures, while still providing significant motion limitation in all motions except weight bearing dorsiflexion (in comparison to no tape). Limiting excessive inversion while simultaneously allowing closer to normal ROM in all other planes may decrease the risk of negatively impacting kinetic chain kinematics associated limited mobility of the ankle.